2013
DOI: 10.1080/01690965.2013.772213
|View full text |Cite
|
Sign up to set email alerts
|

The effects of addressee attention on prosodic prominence

Abstract: How do speakers accommodate distracted listeners? Specifically, how does prosody change when speakers know that their addressees are multitasking? Speakers might use more acoustically prominent words for distracted addressees, to ensure that important information is communicated. Alternatively, speakers might disengage from the task and use less prominent pronunciations with distracted addressees. A further question is whether prosodic prominence changes globally or if there are effects specific to the most re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 35 publications
2
18
0
4
Order By: Relevance
“…Bard et al, 2000;Bard & Aylett, 2004). This effect joins other findings that duration is modulated on the basis of audience knowledge or behaviour Galati & Brennan, 2010;Rosa et al, 2013).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Bard et al, 2000;Bard & Aylett, 2004). This effect joins other findings that duration is modulated on the basis of audience knowledge or behaviour Galati & Brennan, 2010;Rosa et al, 2013).…”
Section: Discussionsupporting
confidence: 79%
“…Some studies show that listener knowledge or attention has no effect (Bard & Aylett, 2004) others show it does (Rosa et al, 2013), and others show effects limited to intelligibility ratings but not duration (Galati & Brennan, 2010), or only planning regions . This raises questions about exactly which kinds of information about addressees affect speakers' pronunciations, and how they relate to the speakers' own internal processes.…”
Section: Audience Design Effects On Acoustic Reductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, in instruction-giving tasks where participants gave instructions to confederates about where to place objects (e.g. 'the teapot goes on red'), longer pronunciations were used for the determi ner when the addressees were not anticipating them (Arnold, Kahn, & Pancani, 2012) and for the object to be moved when the addressees were multitasking (Rosa, Finch, Bergeson, & Arnold, 2013). In addition, Ito and Speer (2006) showed that if the addressee makes a mistake, the correction by the speaker is produced with a contrastive accent.…”
Section: Design and Stimulimentioning
confidence: 99%
“…For example, Baumann and Grice (2006) suggest that a pitch accent is used to mark either a) the degree of activation of the referent in “the assumed (immediate) consciousness of the listener,” (p. 6), or b) the speaker’s wish to highlight information as noteworthy (see also Baumann & Hadelich, 2003). Another idea is that speakers may use prominent forms when the addressee’s attention is not already on the referent, because more explicit bottom-up input is needed to facilitate processing (Rosa, Finch, Bergeson, & Arnold, 2013, this volume).…”
Section: Information Status and Acoustic Prominencementioning
confidence: 99%